Using Textbook Illustration as Media for Developing Character among Primary Students: Some Research-based Suggestion - Asidigisianti Surya Patria; Siti Mutmainah (Journal of Education and Learning (EduLearn), 2018)
Character building is usually being applied in everyday life at school and at home. It is expected that the character education is not only derived only from the teacher but also will be more attractive when it is included into the textbooks. In this literature study, the data were collected by analysing some research papers which relate to primary students’ visual knowledge and character building theory. The results show that character buildings could be included in the illustrations in elementary school textbooks using the students’ interest in illustrations. The illustration is drawn in the form of an overview of the positive values which touch children’s affective aspects. Hopefully, by cultivating the positive values, it will gradually form good character of the primary students.